Collision of hybrid nanomaterials in an upper-convected Maxwell nanofluid: A theoretical approach - Hanif, Hanifa; Shafie, Sharidan; Roslan, Rozaini; Ali, Anati (Elsevier, 2023)
Many viscoelastic fluid problems are solved using the notion of fractional derivative. However, most researchers paid little attention to the effects of nonlinear convective in fluid flow models with timefractional derivatives and were mainly interested in solving linear problems. Furthermore, the nonlinear fluid models with a fractional derivative for an unsteady state are rare, and these constraints must be overcome. On the other hand, nanofluids are thought to be trustworthy coolants for enhancing the cooling process in an electrical power system. Therefore, this research has been conducted to analyze the unsteady upper-convected Maxwell (UCM) hybrid nanofluid model with a time-fractional derivative. Incorporating the Cattaneo heat flux into the energy equation has increased the uniqueness of the research. The numerical solutions for the coupled partial differential equations describing velocity and temperature are presented using an efficient finite difference method assisted by the Caputo fractional derivative. Significant changes in heat transfer and fluid flow properties due to governing parameters, including the nanomaterial volume fraction, fractional derivative, relaxation time, and viscous dissipation, are graphically demonstrated. The nanomaterial concentration, the fractional derivative parameter, and the relaxation time parameter must all be substantial to manifest a surface heat increase. 2022 The Authors. Published by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).